Five-alarm fudge - DeSmet, Christine (DeSmet, Christine. Fudge shop mystery., 2015)
It's autumn in Fisher's Harbor, Wisconsin, and fudge shop owner Ava Oosterling is busy preparing for the harvest festival and a visit from some royal relatives who live in Belgium. According to Ava's grandpa, a famous divinity fudge recipe from the 1860s- a treat fit for a prince- is hidden somewhere in a local historical church. When a fire in the church reveals the body of a murdered man, it looks life someone is willing to go to any length to possess the valuable secret to the divinity fudge. As Ava searches for the killer- and the recipe- she could use a little divine intervention, because she may have bitten off more than she can chew..."--back cover